Prophecies of Civilizational Collapse 2.0: Michel Houellebecq’s Submission - Thompson, Ewa (Porównania, 2024)
The paper interprets a fictional biography of a French university professor bored with life. He tries the usual medicines: sex and other physical pleasures, debates with peers, and monastery solitude. No remedy seems to work. He fails to pay attention to one of his student lovers who chose commitment to a set of beliefs in Israel over pointless existence in Paris. The novel ends with political power in France passing on to the Muslim Brotherhood. The expected changes in social life follow. The professor allows himself to be carried on by the wave of decisions and beliefs provided by others. The paper argues that, in contrast to Mikhail Bulgakov’s thesis that “cowardice is the greatest sin,” Michel Houellebecq suggests that indolence is the source of our failures.